2020
DOI: 10.3389/fcimb.2020.00423
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus Strains Relieve Loperamide-Induced Constipation via Different Pathways Independent of Short-Chain Fatty Acids

Abstract: Increasing researches have confirmed the relationship between slow-transit constipation and gut microbiota dysbiosis. Many population and animal experiments have identified probiotics as effectors for the relief of constipation symptoms, but the specific mechanism remains unclear. In this intervention study, Lactobacillus rhamnosus strains isolated from five different sources were administered to mice with loperamide-induced constipation, and the impacts of these strains on constipation-related indicators were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Intestinal microbiota at the phylum level involved Firmicutes, Bacteroidetes, Proteobacteria, and Verrucomicrobia, and these phyla accounted for more than 98% of intestinal microbiota ( Guo et al, 2020 ). During loperamide-induced constipation, the relative abundance of Firmicutes decreases and that of Verrucomicrobia increases ( Wang et al, 2020 ). L. rhamnosus CCFM1068 administration has shown to decrease the abundance of the phylum Verrucomicrobia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intestinal microbiota at the phylum level involved Firmicutes, Bacteroidetes, Proteobacteria, and Verrucomicrobia, and these phyla accounted for more than 98% of intestinal microbiota ( Guo et al, 2020 ). During loperamide-induced constipation, the relative abundance of Firmicutes decreases and that of Verrucomicrobia increases ( Wang et al, 2020 ). L. rhamnosus CCFM1068 administration has shown to decrease the abundance of the phylum Verrucomicrobia.…”
Section: Resultsmentioning
confidence: 99%
“…L. rhamnosus CCFM1068 administration has shown to decrease the abundance of the phylum Verrucomicrobia. The ability of L. rhamnosus CCFM1068 to alleviate constipation symptoms was associated with a decreased abundance of Verrucomicrobia ( Wang et al, 2020 ). We found that multi-strain probiotics and synbiotic co-administration significantly decreased the abundance of Verrucomicrobia compared to that of the Lop group, and constipation-relieving effect may be due to the reduction of the Verrucomicrobia phylum ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a recent investigatory study (40) assessing the effects of Lactobacillus rhamnosus on treating loperamideinduced constipation showed variable degrees of symptomatic improvement which were bacterial strain-specific and independent of the previously reported SCFA effects (37,38). Specifically, L. rhamnosus increased serum peptide YY, colonic 5-HT, colonic brain-derived neurotrophic factor, and significantly increased α-diversity, with minor effects on improving β-diversity.…”
Section: Evidence From Animal Modelsmentioning
confidence: 88%